Spin Seebeck Effect in a Hybridized Quantum-Dot/Majorana-Nanowire With Spin Heat Accumulation - Sun, Lian-Liang; Fu, Zhen-Guo (Frontiers in Physics, 2021)
Properties of spin Seebeck effect (SSE) in a quantum dot (QD) connected to a topological superconductor or semiconductor nanowire with strong spin-orbit interaction are theoretically studied by the noneqilibrium Green's function method combined with Dyson equation technique. At low temperatures, Majorana zero modes (MZMs) are prepared at the ends of topological superconductor or semiconductor nanowire, and are hybridized to the QD with spin-dependent strength. We consider that the QD is coupled to two leads in the presence of spin heat accumulation (SHA), i.e, spin-dependent temperature in the leads. We find that the thermopower is spin-polarized when the hybridization strength between the QD and one mode of the MZMs depends on electron spin direction, and its spin-polarization can be effectively adjusted by changing the magnitude of SHA. By proper variation of the spin-polarization of the QD-MZM hybridization strength, magnitude of the SHA, dot level, or the direct coupling between the MZMs, 100% spin-polarized or pure thermopower can be generated. Our results may find real usage in high efficiency spintronic devices or detection of the MZMs, which are under current extensive study. The present model is within the reach of current nano-technologies and may by used in high efficiency spin caloritronics devices.